Household Energy Costs and the Housing Choice Voucher Program: Do Utility Allowances Pay the Bills?. Issue 4 (4th July 2019) - Ray, Anne; Wang, Ruoniu; Nguyen, Diep; Martinez, Jim; Taylor, Nicholas; Searcy, Jennison Kipp
ABSTRACT: Utility bills present a hidden threat to the affordability of a family's housing—unknown before a household moves into a unit, and unpredictable from one month to the next. In theory, tenants receiving Housing Choice Vouchers are shielded from energy cost burdens through utility allowances built into rent subsidies. However, tenants may face actual energy costs that far outstrip allowances, effectively rendering their housing unaffordable. This study compares utility allowances with electric bills for over 19, 000 Housing Choice Voucher households in four Florida cities and identifies household and unit characteristics associated with excessive costs. Nearly half of tenants in the sample faced bills in excess of posted allowances, with households renting single-family homes particularly at risk. On the other hand, state-sponsored affordable housing developments, such as those subsidized by the Low Income Housing Tax Credit, offered voucher tenants the chance to live in modern units with lower energy use and a better fit between costs and the utility allowance. The findings have implications for housing authorities and tenants seeking to reduce energy cost burdens.